Comparison of Learning Outcomes Using Concept Map Media and Audio-Visual Media Developed in The RnD Model in Education Statistics Courses in Odd Semester 2019 Classes of Biology Study Programs - Warsodirejo, Pandu Prabowo; Budianto, Budianto (International Journal for Educational and Vocational Studies, 2020)
This study aims to determine whether there are significant differences between student learning outcomes using media concept maps and Audio-Visual media on educational statistics material in the Biology Education Study Program by teaching using concept map media and Audiovisual media. This type of research is experimental research. The sample in this study was only 1 class, 32 students. Sampling was done by purposive sampling. The results of this study indicate that student learning outcomes use audio-visual media rather than teaching using concept maps, where obtained ð‘‹Ì…1 = 7.806 and SD ð‘‹Ì…1 = 0.788 for Audiovisual Media, while for conventional teaching obtained ð‘‹Ì…2 = 6.333 and SD ð‘‹Ì…2 = 2.224 While the percentage the increase in student learning outcomes of the experimental class was 35.12% and the percentage of the control class increased by 32.20%. The results of data analysis showed t hit> t table (5.43> 2.00). So it can be concluded that there is an influence of the use of audio-visual media on learning outcomes in biology statistical material for the fourth semester of the Biology Education Study Program.